2020
DOI: 10.1039/d0nr03921g
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring morphology to control defect structures in ZnO electrodes for high-performance supercapacitor devices

Abstract: Zinc oxide (ZnO) nanostructures were synthesized in the form of nanoparticles, nanoflowers and nanourchins. Structural. electronic and optical characterization of the samples were done via standard techniques such as X-ray...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…In addition, emulating surface defects of multiscale MO particles could improve the antimicrobial activity in a hydrodynamic environment due to their enhanced ROS production from oxygen vacancies [53][54][55]. In particular, the structures of MO NPs or MPs affected the surface oxygen vacancies, resulting in enhanced ROS generation for antimicrobial perfor-mance based on electron-hole pair generation [55][56][57]. However, in the case of CuO and Cu 2 O particles, CuO particles reduce the superoxide radicals to produce Cu + , and Cu 2 O particles do not generate any superoxide radicals for sustained oxidative stress during redox cycling [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, emulating surface defects of multiscale MO particles could improve the antimicrobial activity in a hydrodynamic environment due to their enhanced ROS production from oxygen vacancies [53][54][55]. In particular, the structures of MO NPs or MPs affected the surface oxygen vacancies, resulting in enhanced ROS generation for antimicrobial perfor-mance based on electron-hole pair generation [55][56][57]. However, in the case of CuO and Cu 2 O particles, CuO particles reduce the superoxide radicals to produce Cu + , and Cu 2 O particles do not generate any superoxide radicals for sustained oxidative stress during redox cycling [58].…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] The origins of ZnO intrinsic defects have been studied by EPR spectroscopy. [20][21][22][23][24] This technique is suitable to understand the role of defect centers, as it provides a direct method for monitoring different paramagnetic states of vacancies and paramagnetic metal ions.…”
Section: Domingos Et Almentioning
confidence: 99%
“…ZnO is an n-type semiconductor with the wurtzite-type hexagonal crystal structure and a band gap of around 3.2 eV. Recent studies [20][21][22][23][24] have suggested the possibility of different electronic states in the band gap associated with negatively charged Zn vacancies and positively charged oxygen vacancies. This could indicate a possible transition from a typical n-type to a p-type ZnO semiconductor and, consequently, the development of new electronic devices.…”
Section: Domingos Et Almentioning
confidence: 99%
“…As observed for other nanomaterials [ 36 , 37 , 38 , 39 ], ZnO optical properties have demonstrated a high sensitiveness to several features, such as morphology [ 11 , 29 , 40 ], growth parameters and precursors [ 41 , 42 ], as well as environmental conditions [ 43 , 44 ]. All these parameters concur in defining the defectiveness, that is the concentration and types of point defects present in the material, of ZnO and the resultant luminescence.…”
Section: Introductionmentioning
confidence: 99%